Variant Profiling of a Large Cohort of 138 Chinese Families With Autosomal Dominant Retinitis Pigmentosa - Xiao, Ting; Xie, Yue; Zhang, Xin; Xu, Ke; Zhang, Xiaohui; Jin, Zi-Bing; Li, Yang (Frontiers in Cell and Developmental Biology, 2021)
Retinitis pigmentosa (RP) is the most common form of inherited retinal dystrophy, and 15–25% of RP is transmitted as an autosomal dominant (ad) trait. The objectives of this study were to establish the variant profile in a large cohort of adRP families and to elucidate the variant spectrum of each adRP gene in Chinese patients. A total of 138 probands clinically diagnosed with RP as a presumed autosomal dominant trait were recruited. All probands underwent ophthalmic examinations by specialists. A combination of molecular screening methods, including targeted next-generation sequencing, Sanger DNA sequencing, and multiplex ligation probe amplification assay, was used to detect variants. We identified heterozygous variants of 11 adRP genes in 73 probands, hemizygous or heterozygous variants of X-linked RP genes in 6 patients, compound heterozygous variants of autosomal recessive RP genes in three pseudo-dominant families, and one heterozygous variant of one ad cone and rod dystrophy gene in one proband. One proband was found carrying both variants in RPGR and FAM161A. The overall detection rate was 59.4% (82/138). We detected 72 distinct disease-causing variants involving 16 RP genes and one cone-rod dystrophy gene; 33 of these variants have not been reported previously. Disease-causing variants were identified in the adRP genes in 52.9% of the families, followed by 4.3% in the X-linked RP genes, and 2.2% in the autosomal recessive genes. The most frequent mutant genes were RHO, PRPF31, RP1, SNRNP200, and PRPF8, which explained up to 78.0% of the genetically diagnosed families. Most of the variants identified in adRP genes were missense, and copy number variations were common (7/20) in the PRPF31 gene. We established the profile of the mutated genes and the variant spectrum of adRP genes in a large cohort of Chinese patients, providing essential information for genetic counseling and future development of therapeutics for retinal dystrophy inherited as a dominant trait.